Problem Pemberian Amnesti oleh Presiden Dalam Perspektif Kepentingan Negara - Rizky Malinto Ramadani; Indra Perwira; Bilal Dewansyah (Universitas Batanghari Jambi, 2021)
Article 14 Paragraph (2) of the 1945 Constitution determines that the President grants amnesty and abolition by taking into account the considerations of the House of Representatives. in the provisions of Article (1) of the Emergency Law no. 11 of 1954 concerning Amnesty and Abolition states that